(untitled) (The Informal: South Asian Journal of Human Rights and Social Justice, 2025)
The internet was once hailed as a space of empowerment and open discourse, where marginalized voices could be raised, debate could thrive, and power could be challenged. Today, the internet in South Asia is increasingly constrained by repressive cyber laws, state overreach, and digital censorship, threatening the fundamental right to freedom of expression. This article critically examines the growing disjunction between constitutional safeguards and their enforcement in Nepal, India, and Bangladesh, where vague and draconian legal frameworks, such as Nepal’s Electronic Transactions Act and proposed Social Media Bill, India’s Information Technology Act and Unlawful Activities (Prevention) Act, and Bangladesh’s Digital Security Act and Cyber Security Ordinance, are weaponized to silence journalists, activists, and citizens. Grounded in the theories of shrinking civic space, John Stuart Mill’s harm principle, and Jürgen Habermas’ public sphere, the article uses doctrinal legal research and case analysis to explore how these laws violate international human rights standards, particularly Article 19 of the ICCPR. Key cases, involving journalist Dil Bhusan Pathak (Nepal), comedian Kunal Kamra (India), and activist Mushtaq Ahmed (Bangladesh), reflect a regional pattern of digital authoritarianism. Tactics such as internet shutdown, surveillance, platform censorship, and criminal defamation suppress dissenting voices. Often justified in the name of national security or public order, these measures normalize self-censorship and erode digital civic space. By mapping legal developments and converging authoritarian practices, including the criminalization of satire and suppression of dissent, the article underscores the erosion of press freedom and democratic accountability. It advocates for legal reforms, platform transparency, and sustained advocacy to protect online expression in South Asia.